The admissibility of opening a new field of study by a private university undergoing restructuring proceedings - Adamus, Rafał (The Opole Studies in Administration and Law, 2021)
This study deals with the issue at the interface between constitutional rights and freedoms in the Republic of Poland, administrative law and insolvency law. The question arises whether the Law on Higher Education and Science constitutes the basis for the Minister of Education and Science to refuse to grant permission for the establishment of new majors by a university in restructuring, due to the university’s failure to regulate the arrangement obligations in the restructuring, covered by the statutory moratorium on their repayment? The above dilemma may be the subject of an interesting legal dispute. On the one hand, the right to education must be taken into account. On the other hand, financial stability is required from a university creating a new field of study. The study presents the view in which the establishment of a new field of study by a university under restructuring is allowed. It is also a contribution to research on the legal position of an “atypical” debtor in restructuring.